Predispose, precipitate, perpetuate, and protect: how diet and the gut influence mental health in emerging adulthood - Warren, Michael; O’Connor, Colleen; Lee, Ju Eun; Burton, Jeremy; Walton, David; Keathley, Justine; Wammes, Michael; Osuch, Elizabeth (Frontiers in Nutrition, 2024)
Medicine often employs the 4Ps of predisposing, precipitating, perpetuating and protective factors to identify salient influences on illness states, and to help guide patient care. Mental illness is a significant cause of morbidity and mortality worldwide. Mental health is a complex combination of biological, psychological, environmental and social factors. There is growing interest in the gut-brain-microbiome (GBM) axis and its impact on mental health. We use the medical model of the 4Ps to explore factors involving the connection between nutrition and the GBM axis and their associated risks with mental health problems in emerging adults (EAs), a life stage when mental illness onset is the most common. We review the impact of current dietary trends on the GBM and on mental health, and the role that gut microbiome-based interventions can have in modulating the GBM axis of EAs. We discuss the implications of gut health on the GBM and areas for clinical intervention.